Análise do controle postural de idosas saudáveis - Lemos, Priscilla do Valle (2009)
Introduction: The postural control, fundamental to performance of ADLs, decreases with age advance, causing an increase in body sway and helping to increase the risk of falls. Objective: To analyze the postural control in bipedal support of Brazilian elderly, sedentary and healthy, living in the community and identify if there is correlation between body sway and performance in physical and functional tests, muscle strength, positional sense, age, BMI, activity level and fear of falling. Methodology: An exploratory transversal study on postural performance of 14 healthy elderly, sedentary, with 65 to 85 years. Inclusion criteria: age (65 to 85 years), female, sedentary and absence of falls in the last 12 months. Exclusion criteria: amputation / prosthetic MMII, assistive devices to orthostasis, cognitive decline by MMES, visual/hearing impairment that prevents the tests, history of fracture of lower limbs or spine and ankle sprain in 6 months, stroke and other neurological symptomatic diseases, OA of the knee or hip and other rheumatic diseases, insulin dependent diabetes, dizziness or pain limiting the last 3 months, drug, alcohol and benzodiazepines long-term use. The participants were assessed using a multidimensional questionnaire, stabilometry and torque of knee and ankle evaluation and ankle proprioception. We used measures of central tendency in the descriptive data of the quantitative continuous or discrete distribution and relative frequency for the nominal and ordinal categorical. Adherence to normality was verified using Shapiro-Wilk test. Pearson's correlation tests coefficient were used to analyze the correlation between variables of body sway, muscle strength, proprioceptive acuity, physical and functional tests (SPPB, TUG and TUGM), BMI, PHA and FESI. Level of significance p<0.05. The data were analyzed with SPSS software, version 10.0. Results: Mean age, body weight and height were 73.57 +6.74 years, 61.64 +12.47 kg and 1.51 +0.45 meters. Relative frequency of PAH was 42.86% of elderly moderately active and 57.14% of active elderly. There was no correlation between physical measurements of body sway and age. It was found substantial negative correlation between: PAH and DTPPSROF (r =- 0.606 and p = 0.011), torque set to work the hip extensors and DTPPSMOA (r =- 0.616 and p = 0.010), adjusted torque to the work of the ankle flexors and DTPPSMOA (r =- 0.590 and p = 0.013), torque set to work of the ankle and DTPPSROF (r =- 0.607 and p = 0.011), and between the DTPPSROA and BMI (r =- 0.58 p = 0.03). Substantial positive correlation between: FESI and DTPPSMOA (r = 0.514 and p = 0.030), total work of the hip extensors and DTPPSROA (r = 0.622 and p = 0.009), and between the DTPPSMOF and DTPPSMOA (r = 0.50 and p = 0, 07). Conclusion: There was no correlation of any of the four sensory conditions with BMI, hip flexor muscles, positional sense and ankle extensor muscles of the ankle. Negative correlation was found between the flexor muscles of the ankle and DTPPSMOA and DTPPSROF, and between PAHs and body sway in condition PPSROF. The hip extensor muscles had a negative correlation with DTPPSMOA and positive correlation between hip extensors and DTPPSROA. The FESI had positive correlation with the DTPPSMOA